2016
DOI: 10.1002/pc.23902
|View full text |Cite
|
Sign up to set email alerts
|

Study on dynamic mechanical, thermal, and mechanical properties of long glass fiber reinforced thermoplastic polyurethane/poly(butylene terephthalate) composites

Abstract: Long glass fiber reinforced thermoplastic polyurethane and Poly (butylene terephthalate) (PBT) (LGFTP) composites with different ratios of TPU and PBT were prepared by using self-designed impregnation device. The dynamic mechanical, thermal, and mechanical properties of LGFTP composites were studied. Results showed that there was good compatibility between TPU and PBT. Dynamic mechanical thermal analysis (DMA) results indicated that the TPU content and scanning frequencies had some influence on dynamic mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Improving the properties linked with impacts makes resistance to flexion and storage modulus worse. Zhang et al [28] ran tests with thermoplastic polyurethane (TPU). Dynamic mechanical analysis (DMA) indicated that the addition of TPU increases tensile and notched Izod impact strength with a small reduction in flexural strength and modulus.…”
Section: Introductionmentioning
confidence: 99%
“…Improving the properties linked with impacts makes resistance to flexion and storage modulus worse. Zhang et al [28] ran tests with thermoplastic polyurethane (TPU). Dynamic mechanical analysis (DMA) indicated that the addition of TPU increases tensile and notched Izod impact strength with a small reduction in flexural strength and modulus.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 To improve mechanical and thermal properties, glass fiber is the most widely used reinforcing material in PBT and its blends. 321…”
Section: Introductionmentioning
confidence: 99%
“…This trend is caused by the physical combination between fibers and the polymer melt, indicating that the presence of TPU constrains the displacement of carbon fiber tows during the tensile process, enhancing the strain and improving energy absorption. [25][26][27][28] Furthermore, the control group (without the TPU sheath) exhibits one-time breakage followed by brittleness breakage. The TPU sheath ensures the experimental groups undergoing two-stage fractures, which are separately attributed to the carbon fiber tows that provide mechanical support and the TPU sheath that offers ductility.…”
Section: Resultsmentioning
confidence: 99%